EFFICIENCY OF STEP AEROBIC ON TRANSFORMATIONS OF ANTROPOMETRIC CHARACTERISTICS MOTORIC ABILITIES OF STUDENTS - Muris Đug; Branimir Mikić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
The main goal of this research is determining of effi ciency of two months step aerobic training on quantitative differences in the area of antropometric characteristics and in the area of motoric abilities at students of Tuzla University. The size of sample consists of 21 male student. It is visable from presented analisis, and results of two months-two times a week training, from the beginning and on the end of step aerobic training, tested with t-test, that there are evident effects in the area of antropometric characteristics and in the area of motoric abilities at students of Tuzla University